Aerodynamic Performance of the Three-Dimensional Lumped Flexibility Bionic Hovering Wing - Zhu Jianyang; Jiang Lin; Hou Yu (International Journal of Aerospace Engineering)
Understanding the effect of flexibility on the aerodynamic characteristics of the wing is one of the most important considerations for successfully designing a flapping wing micro aero vehicle (FMAV). This paper aims at providing a systematic synthesis on the flexibility effects on the hovering performance of the bionic wing based on the numerical analysis approach. We construct a novel three-dimensional bionic wing, which has lumped flexibility at the root, and develop an iterative coupling program to simulate the interaction between the flexible wing and fluid. The effects of flexibility on the hovering performance of the three-dimensional flapping wing are investigated, and the results indicate that the best performance of the wing is achieved when the wing flaps at resonance and has the density close to the natural insect wing. The feasibility of using lumped flexibility wings driven by a simple harmonic flapping for designing efficient FMAV is also concluded in this study.